Do the Economic Growth, PAD, DAU and DAK Fluctuations Effect on Capital Expenditures? - Pratiwi, Azhara Oktavianita; Sari, Imelda (Santoso Academy Network, 2024)
This research aims to determine the effect of economic growth, fluctuations in local revenue, fluctuations in general allocation funds, and fluctuations in special allocation funds on capital expenditure. The data in this research is secondary data obtained from the Republic of Indonesia Financial Audit Agency (BPK RI). This research uses data from Regional Government Financial Reports (LKPD) regarding Gross Regional Domestic Product (PDRB) and Regional Revenue and Expenditure Budget Realization Reports (APBD) for Regencies/Cities throughout South Sumatra for 2018-2020. The data analysis technique used is quantitative analysis. The results of this research partially show that the variables Fluctuations in Regional Original Income and Fluctuations in Special Allocation Funds influence Capital Expenditures. Meanwhile, the Economic Growth and General Allocation Fund Fluctuations do not affect Capital Expenditures. Managerial implications suggest that regional governments should enhance revenue stability and strategically manage fund allocations to ensure consistent and sustainable capital investments. This approach will enable better financial planning and improved infrastructure development, ultimately fostering regional economic growth and development.